The Influence of Land Use and Land Cover on Surface Temperature in a Water Catchment Sub-Basin - Santos, Arthur Pereira Dos [UNESP] (2023)
Faced with the recent crises of water capture and distribution, managing water resources is a practice that has been gaining prominence in discussions and debates about environmental issues. Thus, this article aims to analyze, in a spatio-temporal way, the Changes in Land Use and Occupation (LULC) and Surface Temperature (LST) in the water catchment sub-basin of Ribeirão Santa Isabel, located in the municipality of Paracatu, Minas Gerais (MG), between the years 1990 and 2020. The choice of the area is justified by the conflicts of use that encompass the sub-basin and by the fact that this is the only source of capture in the municipality, which has already carried out the alteration of the water resource responsible for the capture of water due to the intensity of agricultural practices in the region in the previous area. Through geoprocessing and Remote Sensing (RS) techniques, images from the Landsat-5 and Landsat-8 satellites were used to perform the LST calculations. Regarding usage and occupancy data, the images provided by the Mapbiomas platform were used. It was verified, through the increase in the percentage of the water class and vegetation and the decrease in the agricultural class, that the practices implemented in the study area, in order to conserve the remnants of the biome and maintain a good water availability to the municipality, are having an effect. It was also possible to conclude that LST is affected by LULC, and that the greatest variations occur in non-vegetated areas.